Acceptability of a dapivirine levonorgestrel vaginal ring in two Phase 1 trials (MTN-030/IPM 041 and MTN-044/IPM 053/CCN019): Implications for multipurpose prevention technology development. - Barbara A Friedland; Holly Gundacker; Sharon L Achilles; Beatrice A Chen; Craig Hoesley; Barbra A Richardson; Clifton W Kelly; Jeanna Piper; Sherri Johnson; Brid Devlin; John Steytler; Kyle Kleinbeck; et al. (PLoS ONE)
End-user feedback early in product development is important for optimizing multipurpose prevention technologies for HIV and pregnancy prevention. We evaluated the acceptability of the 90-day dapivirine levonorgestrel ring (DPV-LNG ring) used for 14 days compared to a dapivirine-only ring (DVR-200mg) in MTN-030/IPM 041 (n = 23), and when used for 90 days cyclically or continuously in MTN-044/IPM 053/CCN019 (n = 25). We enrolled healthy, non-pregnant, HIV-negative women aged 18-45 in Pittsburgh, PA and Birmingham, AL (MTN-030 only). Self-reports of vaginal bleeding and adherence (ring removals, expulsions) were collected via daily short message service. Acceptability data were recorded in face-to-face interviews at study exit. We assessed differences in acceptability by product characteristics and adherence; and associations between baseline characteristics/demographics, number of bleeding days, adherence, and overall acceptability. Most (21/23) women in the 14-day MTN-030 study and about half (13/25) in the 90-day MTN-044 study liked their assigned rings. In MTN-030 there were no significant associations between any variables and overall acceptability of either ring. In MTN-044, women who disliked the DPV-LNG ring had a significantly higher incidence of unanticipated vaginal bleeding, and reporting that vaginal bleeding changes were unacceptable than those who liked it. Although we found no overall association between adherence and acceptability, significantly more women who disliked (versus liked) the DPV-LNG ring reported expulsions during toileting. The DPV-LNG ring could meet the needs of women seeking simultaneous protection from HIV and unintended pregnancy. Addressing issues related to vaginal bleeding and expulsions early in product development will likely enhance acceptability of the DPV-LNG ring. Trial registration: Clinical Trial Registration: MTN-030/IPM 041: ClinicalTrials.gov NCT02855346; MTN-044/IPM 053/CCN019: ClinicalTrials.gov NCT03467347.